A real-time controller for sustaining thermally relevant acoustic cavitation during ultrasound therapy. - Hockham, N; Coussios, C; Arora, M (2010)
A novel method for sustaining inertial cavitation during high-intensity focused ultrasound (HIFU) exposure in an agar-based tissue-mimicking material is presented. Inertial cavitation occurs during HIFU therapy when the local rarefaction pressure exceeds the inertial cavitation threshold of the insonated medium, and is characterized by broadband acoustic emissions which can be easily detected non-invasively using a passive cavitation detector (PCD). Under the right conditions, inertial cavitation has been previously shown to greatly enhance the rate of heat deposition by redistributing part of the energy carried at the fundamental HIFU frequency to higher frequencies, which are more readily absorbed by visco-elastic media such as soft tissue. However, in the absence of any cavitation control, inertial cavitation activity at the focus decays rapidly over a few seconds of exposure because of the combined effects of cavitation nuclei depletion, bubble dissolution, bubble-bubble interactions, increased vapor pressure caused by heating, and focal shielding caused by pre-focal bubble activity. The present work describes the design, validation, and testing of a real-time adaptive controller, with integrated passive localization capabilities, for sustaining inertial cavitation within the focal region of a HIFU transducer by modulation of the HIFU amplitude. Use of the controller in agar gel, originally at room temperature, has enabled therapeutically relevant temperatures in excess of 55°C to be maintained continuously in the focal region for more than 20 s using significantly less acoustic energy than is required to achieve the same temperature rise in the absence of cavitation control.